Motivators of couple HIV counseling and testing (CHCT) uptake in a rural setting in Uganda. (December 2017) - Nannozi, Victoria; Wobudeya, Eric; Matsiko, Nicholas; Gahagan, Jacqueline
Abstract Background Couple HIV Counseling and Testing (CHCT) is one of the key preventive strategies used to reduce the spread of HIV. In Uganda, HIV prevalence among married/living together is 7.2% among women and 7.6% among men. CHCT can help ease disclosure of HIV-positive status, which in turn may help increase opportunities to get social support and reduce new infections. The uptake of CHCT among attendees of health facilities in rural Uganda is as high as 34%. The purpose of this study was to explore the motivators of CHCT uptake in Mukono district, a rural setting in Uganda. Methods The study was conducted in two sub-counties in a rural district (Mukono district) about 28 km east of the capital Kampala, using a descriptive and explorative qualitative research design. Specifically, we conducted focus group discussions and key informant interviews with HIV focal persons, village health team (VHT) members, religious leaders and political leaders. We also interviewed persons in couple relationships. Data was analysed using NVivo 8 software. Ethical clearance was received from the Mengo Hospital Research Review Board and from the Uganda National Council of Science and Technology. Results The study was conducted from June 2013 to July 2013 We conducted 4 focus group discussions, 10 key informant interviews and interviewed 53 persons in couple relationships. None of the participants were a couple. The women were 68% (36/53) and 49% (26/53) of them were above 29 years old. The motivators of CHCT uptake were; perceived benefit of HIV testing, sickness of a partner or child in the family and suspicion of infidelity. Other important motivators were men involvement in antenatal care (ANC) attendance and preparation for marriage. Conclusion The motivators for CHCT uptake included the perceived benefit of HIV testing, sickness of a partner or child, preparation for marriage, lack of trust among couples and men involvement in antenatal care. Greater attention to enhancers of CHCT programming is needed in trying to strengthen its uptake.